Optimal observer-based control design for aircraftlateral motion - Komnatska, M. M.; Kiliian, I. V.; Berezanskyi, Y. A. (Problems of Informatization and Control, 2015)
The paper presents an alternative approach of observer-based flight control system design. Thisapproach is based on the application of linear matrix inequality technique. The design proceduretreats the design of both observer and controller by solving the set of linear inequalitiessimultaneously. The proposed approach is free of observer poles placement location. Simulationresults demonstrate the validity and effectiveness of the proposed design approach